Retracted: Classification of Myopathy and Amyotrophic Lateral Sclerosis Electromyograms Using Bat Algorithm and Deep Neural Networks - Neurology, Behavioural (Behavioural neurology, 2023)
[This retracts the article DOI: 10.1155/2022/3517872.].